2021
DOI: 10.1101/2021.03.24.436813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress is basic: ABA alkalinizes both the xylem sap and the cytosol of Arabidopsis vascular bundle sheath cells by inhibiting their P-type H+-ATPase and stimulating their V-type H+-ATPase

Abstract: BACKGROUND AND HYPOTHESIS•Under water deprivation, in many perennial species, the stress hormone, ABA, appears in the xylem sap in the shoot (including leaf) veins and the xylem sap pH (pHEXT) increases. This study aimed to test the hypothesis that ABA is the signal for an altered proton balance of the leaf-vein-enwrapping bundle sheath cells (BSCs).METHODS•Plant Material. We used a few Arabidopsis thaliana (L.) Heynh. genotypes: wildtype (WT) of two accessions, Landsberg erecta (Ler) and Columbia (Col), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…In particular, Prado et al ( 2019) demonstrated a contribution of the abundantalso in the leaf veinsaquaporin AtPIP2;1 to the diurnal and circadian rhythms of the hydraulic conductance of the Arabidopsis rosette, K ros , which peaked before midday. Thus, in addition to the likely Pf-promoting effect of the slightly acidic pH (6) perfusion solution (a link established by Grunwald et al, 2021), that Prado et al, (2019 used for their Kros measurements, the changes that they observed in Kros also reflected the effects of light and circadian rhythms (Prado et al, 2019). Thus, light-induced changes in aquaporin activity underlying the effects of light on Kros are consistent with light-induced increase of Pf that we observed.…”
Section: Light Induces the Increase Of Bscs' Membrane Water Permeability Kleaf And Krosmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, Prado et al ( 2019) demonstrated a contribution of the abundantalso in the leaf veinsaquaporin AtPIP2;1 to the diurnal and circadian rhythms of the hydraulic conductance of the Arabidopsis rosette, K ros , which peaked before midday. Thus, in addition to the likely Pf-promoting effect of the slightly acidic pH (6) perfusion solution (a link established by Grunwald et al, 2021), that Prado et al, (2019 used for their Kros measurements, the changes that they observed in Kros also reflected the effects of light and circadian rhythms (Prado et al, 2019). Thus, light-induced changes in aquaporin activity underlying the effects of light on Kros are consistent with light-induced increase of Pf that we observed.…”
Section: Light Induces the Increase Of Bscs' Membrane Water Permeability Kleaf And Krosmentioning
confidence: 99%
“…Plant genotypes. We used WT (wild type) Arabidopsis thaliana plants ecotype Colombia, Col-0 (aka Col), the T-DNA insertion AHA2 mutants aha2-4 (SALK_ 082786) (Col) and aha2-4 complemented with SCR: AHA2 (line 56) (Col), and SCR:GFP (Col) as described previously (Grunwald et al, 2021). In addition, we used WT Arabidopsis (Col) with the glabrous mutation (WT Col-gl), phot1-5 (nph1-5) (Col-gl), phot 2-1 (npl1-1 or cav1-1) (Col-gl) and the double mutant phot1-5phot2-1 (nph1-5 npl1-1) (Col-gl) (Kagawa et al, 2001), which were kindly provided by the Ken-Ichiro Shimazaki lab (Tokyo, Japan).…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations